Implementasi Pembelajaran Sosial Pembiasaan Diri Bershodaqoh di Sekolah dalam Membentuk Kepribadian Anak (Studi Kasus di MI Perguruan Mu’allimat Cukir Jombang) - Enik Khorida (MODELING: Jurnal Program Studi PGMI, 2016)
Learning an activity undertaken by teachers in a way that student behavior changed for the better. In this case the behavioral changes include changes in behavior of the intellectual, religious and sosial. Habituation themselves bershodaqoh This is one sosial learning has an important role in shaping the personality of the child. Among them are self habituation bershodaqoh able to nurture the soul concerned with the environment in children. Therefore, activities in the sosial learning in particular habituation bershodaqoh themselves should not be underestimated and overlooked. Reality is what has driven education practitioners to solve these problems, the goal of researchers such as to know the concept of sosial learning in school bershodaqoh habituation themselves and the implementation of sosial learning in school bershodaqoh habituation themselves in shaping the personality of the child. This research uses qualitative (Grounded) Data collected by interview, observation and documentation. The form of the data are the words, notes, reports, and documents obtained from the principal, teachers, and students MI College Mu'allimat. Data analysis is done by means of data reduction, data presentation, and conclusion. From this research, it was found that sosial learning through self habituation bershodaqoh d MI College Mu'allimat ,. Based on these studies the researchers discovered a proposition that if the school is able to construct a sosial learning tool, it will form the desired child's personality through self-bershodaqoh habituation. The authors suggest that to obtain optimal results in doing any activity, hence the need to shape the personality of the child learn sosial mainly self bershodaqoh habituation. Because this research is still far from perfection, therefore it is expected to examine more deeply to serve as a reference for further research.